2021
DOI: 10.2147/jaa.s280247
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Airway Smooth Muscle Hypertrophy in Asthma: An Approach Whose Time Has Come

Abstract: Airway smooth muscle (ASM) cell dysfunction is an important component of several obstructive pulmonary diseases, particularly asthma. External stimuli such as allergens, dust, air pollutants, and change in environmental temperatures provoke ASM cell hypertrophy, proliferation, and migration without adequate mechanistic controls. ASM cells can switch between quiescent, migratory, and proliferative phenotypes in response to extracellular matrix proteins, growth factors, and other soluble mediators. While some as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…In addition, increased pericyte recruitment to vessels caused by a loss of prolyl hydroxylase domain protein 2 in ECs leads to perivascular fibrosis, right ventricular hypertrophy, and PH independent from any other stimuli [ 140 ]. Hypertrophic airway smooth muscles can limit apoptosis in neighboring myofibroblasts [ 154 ], and such effects may further the vascular remodeling observed in pulmonary vessels.…”
Section: Vascular Pericytes In Pulmonary Fibrosismentioning
confidence: 99%
“…In addition, increased pericyte recruitment to vessels caused by a loss of prolyl hydroxylase domain protein 2 in ECs leads to perivascular fibrosis, right ventricular hypertrophy, and PH independent from any other stimuli [ 140 ]. Hypertrophic airway smooth muscles can limit apoptosis in neighboring myofibroblasts [ 154 ], and such effects may further the vascular remodeling observed in pulmonary vessels.…”
Section: Vascular Pericytes In Pulmonary Fibrosismentioning
confidence: 99%
“…Frontiers in Physiology frontiersin.org myofibroblasts by modulating apoptosis (Chetty and Nielsen, 2021).…”
Section: Contribution Of Pericytes To Subepithelial Fibrosis In Aller...mentioning
confidence: 99%
“…Hypertrophy of SMCs increases their contractility and therefore contributes to airway hyperresponsiveness. It has also been suggested that hypertrophic smooth muscle may have a protective effect on neighbouring myofibroblasts by modulating apoptosis ( Chetty and Nielsen, 2021 ). The increased number of SMCs also increases the contraction of airways as well as the responsiveness of the cells to stimuli ( Khan, 2013 ).…”
Section: Allergic Asthma—symptoms Disease Course and Pathological Mec...mentioning
confidence: 99%
“…Fortunately, understanding the mechanisms by which sex steroids influence structural cells of the airways has garnered new interest with novel findings from researchers working on ASM, epithelial cells and fibroblast in the lungs [ 5 , 39 , 201 , 207 , 208 ]. Sex steroids influence structural cells of the airways and immune cells independently.…”
Section: Sex Steroids and Structural Cells Of The Airwaymentioning
confidence: 99%